Study on the Production Decline Characteristics of Shale Oil: Case Study of Jimusar Field - Luo, Shuanghan; Su, Hao (Frontiers in Energy Research, 2022)
The productivity of horizontal shale oil wells is low. To achieve cost-effective development, hydraulic fracturing techniques are often used. After hydraulic fracturing, wells have a high initial production rate. After a period of production, the production rate will decline rapidly and then remain low for an extended period of time. The study of the decline characteristics of horizontal wells is of great importance. We have collected development data from 94 horizontal wells in the Jimusar field. Some classical decline curve methods, such as the “power law–loss ratio” rate decline model, the stretch exponential equation, and the Duong decline curve, can be used to fit the production history. For example, Wells JHW018, JI172_H, and JI36_H were analyzed for production variations at different stages after the onset of production decline. On the basis of the performance of the parameters in typical wells, it was found that only Valko extended decline curves could be used to obtain satisfactory prediction results. A controlled fracture decline rate is proposed to describe the extent of the initial decline. The findings of this study can help for better predict of shale reservoir production after volume fracturing.